Institutional economics and transition economies: Some analytical issues - Wei Ge (Transformation, Integration and Globalization Economic Research (TIGER), 2006)
It is argued in literature that two schools of thoughts might have been most relevant and influential to the policy formation and implementation in transition economies, with distinguishable economic and social outcomes. While Russia and some countries in the Central and Eastern Europe have commonly been perceived as the subscribers to 'the Washington consensus,' the transition practice in China is seen by some as a vindication of 'the evolutionary-institutionalist perspective.' This study attempts to assess the validity of this latter argument and, on that basis, to raise some analytical issues which may warrant further scholarly investigations. These include the role of the government in transition economies, the characteristics of China's 'gradualist' approach, the essence of an economic transition and the criteria for assessing its progress. For the benefit of a fruitful analysis, these issues need to be more carefully addressed.
Keywords: 330; Systemtransformation; Systemtransformation; Institutionenökonomik